Preliminary findings on the correlation of saliva pH, buffering capacity, flow rate and consistency in relation to waterpipe tobacco smoking. Issue 1 (1st January 2017) - Khemiss, Mehdi; Ben Khelifa, Mohamed; Ben Saad, Helmi
ABSTRACT: The aim of the present comparative study was to compare some salivary characteristics between exclusive waterpipe smokers (EWPS) and non-smokers. 72 males (36 EWPS) were recruited. The volume of stimulated saliva was determined and divided by the duration of saliva collection. The pH was measured directly using a pH meter. The buffering capacity was determined using a quantitative method which involved the addition of 10 µl HCl. Up to a total of 160 µL was titrated up to obtain a pH titration curve. At 50 µL of titrated HCl, buffering capacity was ranked into three categories: high, medium and low. EWPS and non-smoker groups had similar flow rates (1.81 ± 0.79 and 1.78 ± 1.14 mL min-1) and similar baseline pH (6.60 ± 0.37 and 6.76 ± 0.39). Statistically significant differences in the two groups' pH were observed from 30 to 160 µL of titrated up HCl. At 50 µL of titrated up HCl, the EWPS group compared to the non-smoker group had a significantly higher pH (4.79 ± 0.72 vs. 5.32 ± 0.79). To conclude, waterpipe tobacco smoking alters the buffering capacity but does not alter either salivary flow rates or the baseline pH and consistency.